A real-world pharmacovigilance analysis of ALK inhibitor-associated pleural and pericardial effusion using the FDA Adverse Events Reporting System (FAERS) database from 2013 to 2024. - Connor Frey (PLoS ONE)
Introduction The advent of anaplastic lymphoma kinase (ALK) inhibitors has revolutionized the treatment of ALK-rearranged malignancies, establishing these agents as vital components of precision oncology. Despite their proven efficacy in prolonging progression-free and overall survival, ALK inhibitors are associated with notable adverse events, particularly cardiopulmonary complications such as pleural and pericardial effusions. Methods This study investigates the real-world prevalence and risk of these effusions associated with five ALK inhibitors, crizotinib, ceritinib, alectinib, brigatinib, and lorlatinib, through disproportionality analysis using the FAERS pharmacovigilance database. Results The data revealed elevated reporting odds ratios (RORs) for pleural and pericardial effusions, with notable variability among the agents. Crizotinib exhibited RORs of 7.76 (95% CI: 6.60-9.12) and 9.00 (95% CI: 7.10-11.41) for pleural and pericardial effusions, respectively. Ceritinib demonstrated RORs of 7.36 (95% CI: 5.16-10.50) and 10.80 (95% CI: 6.79-17.19), respectively. Alectinib showed lower RORs of 4.76 (95% CI: 3.80-5.97) and 6.67 (95% CI: 4.92-9.04). Brigatinib displayed elevated RORs of 8.70 (95% CI: 6.58-11.52) and 7.87 (95% CI: 4.95-12.51). Lorlatinib presented the highest risk, with RORs of 8.61 (95% CI: 6.72-11.02) and 12.57 (95% CI: 9.08-17.38). Conclusions This study highlights the critical need for vigilant pharmacovigilance and a multidisciplinary approach to balance the oncologic benefits of ALK inhibitors against their cardiopulmonary risks. By enhancing awareness and fostering proactive management, these findings aim to support the safe and effective use of ALK inhibitors in treating ALK-rearranged malignancies.